Les prémices de l’architecture métallique en Guadeloupe : la construction de l’église Saint-Pierre et Saint-Paul de Pointe-à-Pitre au XIXe siècle - Bruno Kissoun (In Situ)
The inventory survey of the historic centre of Pointe-à-Pitre was undertaken in 2001. The present article is the result of three years’ research on the church of Saint-Paul and Saint-Pierre, a particularly emblematic monument and the only building that still bears witness to the troubled history of the city, cruelly hit by natural disasters from the eighteenth century. Technically, it was an innovatory building which, from the middle of the nineteenth century, sought to replace traditional building materials with iron. The use of iron elements was at first only timid, but gradually iron structures came to be used throughout the building. The church may be seen then as a precursor in the use of iron in the religious buildings of the French colonies.